Binge eating disorder: What are the differences in emotion regulation, impulsivity, and eating behaviors according to weight status?. (December 2022) - Hanras, Eva; Boujut, Emilie; Ruffault, Alexis; Messager, Diane; Rives-Lange, Claire; Barsamian, Charles; Carette, Claire; Lucas-Martini, Léa; Czernichow, Sébastien; Dorard, Géraldine
Abstract: The emotional and eating characteristics of individuals with both obesity and binge eating disorder (BED) and those with obesity without BED have been widely studied. However, it is unclear whether the difficulties of these individuals are attributable to BED or obesity. The principal objective is to compare the emotional difficulties, impulsive traits, and eating styles of individuals diagnosed with BED with those of individuals without BED based on their weight (i.e., obesity, overweight, normal weight). The second objective is to compare these components according to their weight status in individuals living with BED. The 429 participants responded to a diagnostic interview to assess the presence of eating disorders and filled out questionnaires evaluating emotions (positive and negative emotions, emotional competencies, and regulation strategies), impulsive traits, and eating styles. Group comparisons between individuals with BED (presence/absence) according to their weight statuses were calculated. Participants with BED have more emotional and eating difficulties and engage in more impulsive behaviors than individuals without BED of the same weight. There were few differences between normal weight, overweight, and obese individuals with BED. Although BED has been little investigated among normal-weight individuals, this study shows that it is necessary to evaluate this eating disorder in this population to offer them adequate support and prevent weight gain. Highlights: Individuals who are overweight/obese and BED have more emotional, impulsivity, and eating difficulties than no-BED. Normal-weight individuals with BED have more emotional eating difficulties than those without BED. Weight status does not influence the difficulties experienced by individuals with BED.